The world of learning, 2000 (Europa Pub., 1999)
This reference lists over 26,000 universities, colleges, schools of art and music, libraries, learned societies, research institutes, museums and art galleries - arranged alphabetically by country. It also lists professors at major universities by name together with the subjects they teach.